2019
DOI: 10.1080/21505594.2019.1682761
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrolipoamide dehydrogenase ofVibrio splendidusis involved in adhesion toApostichopus japonicus

Abstract: Vibrio splendidus is one of the most opportunistic marine pathogens and infects many important marine animals, including the sea cucumber Apostichopus japonicus. In this study, two genes named DLD1 and DLD2, encoding dihydrolipoamide dehydrogenase (DLD) homologues in pathogenic V. splendidus, were cloned, and conditionally expressed in Escherichia coli BL21 (DE3). The enzymatic activities of DLD1 and DLD2 showed that they both belonged to the NADH oxidase family. Both DLD1 and DLD2 were located on the outer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Next, mgrA , a global regulator, has been found to affect several efflux pumps in S. aureus , such as norA and norB for MDR, and tet38 for tetracycline resistance ( 96 , 97 ). Gene pdhD encodes a membrane protein, dihydrolipoyl dehydrogenase (DLD), which belongs to the oxidoreductase family and is essential for energy metabolism ( 98 ). In Vibrio parahaemolyticus , DLD levels were upregulated in antimicrobial peptide-resistant clones at both translational and transcriptional levels ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next, mgrA , a global regulator, has been found to affect several efflux pumps in S. aureus , such as norA and norB for MDR, and tet38 for tetracycline resistance ( 96 , 97 ). Gene pdhD encodes a membrane protein, dihydrolipoyl dehydrogenase (DLD), which belongs to the oxidoreductase family and is essential for energy metabolism ( 98 ). In Vibrio parahaemolyticus , DLD levels were upregulated in antimicrobial peptide-resistant clones at both translational and transcriptional levels ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in at least five multi-enzyme complexes and is a necessary component for the complex to complete the reaction. In addition, DLD, as a flavin protein oxidoreductase, accepts proton and electron-catalyzed disulfide bond formation with FAD as a co-group ( Dai et al, 2019 ). Studies have confirmed that DLD is closely related to ferroptosis induced by cystine deprivation or import inhibition, and DLD inhibition can reduce lipid peroxidation and ferrous iron accumulation, thereby inhibiting ferroptosis suppression ( Shin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…DLD of Pseudomonas aeruginosa was found to be a surface-exposed protein that binds the human plasma proteins and may contribute to tissue invasion [ 31 ]. In addition, it was suggested that the DLD of Vibrio is involved in adhesion to cells and tissues of Apostichopus japonicus [ 32 ]. Although the previous findings showed that MRP, GAPDH, and DLD were potential immunogens, their protective efficacy still needs to be improved.…”
Section: Discussionmentioning
confidence: 99%